2021
DOI: 10.31729/jnma.6747
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety and Stress among Nepali Health Care Workers during the Coronavirus Disease 2019 Pandemic: A Cross-sectional Survey

Abstract: Introduction: Studies among health care workers from different part of world during the coronavirus disease 19 pandemic have reported substantial impact on their physical, mental and emotional well-being. This study measured the impact of coronavirus disease 2019 on the mental health of Nepali healthcare workers in different parts of the world during the pandemic. Methods: This cross-sectional survey was carried out from December 25, 2020 to Jan 25, 2021. Ethical approval was taken from the Institutional Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In this study, economic status affected health care workers’ health-related quality of life. This is similar to the results of previous studies [ 30 , 32 ]. This would have included psychologically distress regarding changes in financial conditions, such as salary cuts and job insecurity due to the economic recession caused by the COVID-19 pandemic [ 30 ], which would have affected the health-related quality of life of healthcare workers.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, economic status affected health care workers’ health-related quality of life. This is similar to the results of previous studies [ 30 , 32 ]. This would have included psychologically distress regarding changes in financial conditions, such as salary cuts and job insecurity due to the economic recession caused by the COVID-19 pandemic [ 30 ], which would have affected the health-related quality of life of healthcare workers.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of anxiety and depression found in this study is higher than the prevalence reported in a study using a similar tool among health care workers belonging to different levels of health care facilities from inside and 15 Similarly, a study done among doctors, nurses and paramedics residing in Nepal and abroad, using DASS-21, reported the prevalence of anxiety and depression as 22.5% and 30.05%, respectively, which is higher than the findings of our study. 16 Although those studies were done among different populations using different tools and are not comparable, and the findings can signal the higher burden of mental health problems among health care workers in Nepal.…”
Section: Discussionmentioning
confidence: 98%
“…In order to assess the psychological impact of the COVID-19 pandemic among health professionals, a study carried out in intensive care units of hospitals in Ireland found positive scores in 201 workers (42.6%) for depression and in 213 (45.1%) for anxiety and stress [ 36 ]. Among 208 Nepali health care workers, 62 (30%) participants were positive for anxiety, 47 (22.5%) for depression and 25 (12%) for stress; a higher prevalence of depression 18 (30%) and stress 10 (17%) was found in nurses compared to paramedics [ 37 ].…”
Section: Discussionmentioning
confidence: 99%